Longitudinal Microsurgery Laboratory Training during Hand Surgery Fellowship - Amador, Ricardo O.; Sood, Ravi F.; Wilkens, Suzanne; Gottlieb, Rachel; Chen, Neal C.; Eberlin, Kyle R. (Journal of Reconstructive Microsurgery, 2019)
Background–Laboratory training courses have traditionally offered an attractive method to learn microsurgery in a low-risk environment. However, courses are often limited by cost, accessibility, and their one-time, nonlongitudinal nature. Our aims were to (1) describe our institution's microsurgical training course for hand surgery fellows, which is longitudinal and integrated within our fellowship curriculum and (2) investigate how this course affects the microsurgical confidence and competence of trainees throughout their fellowship year.Methods–All hand fellows who trained in our 1-year combined hand surgery fellowship from 2016 through 2018 participated in this study. Baseline data on the type and duration of residency training, previous microsurgery experience and self-reported confidence, knowledge, and interest in microsurgery were recorded. Self-reported scores were documented using a continuous scale ranging from 0 to 10. An initial 3-day laboratory course combining the use of didactic teaching, a nonliving synthetic model, and a live rat model was conducted. Repeat laboratory training occurred thereafter at 6 and 12 months. At the end of each session, fellows repeated the baseline questionnaire and faculty assessed their microsurgical competence using a standardized global rating scale (GRS).Results–A total of six fellows (2 years) were enrolled. At the end of the initial course, there was a statistically significant increase in mean self-reported confidence in microsurgery from 4.3 to 6.2 and knowledge from 4.7 to 6.5. Mean scores in interest were unchanged, from 9.2 to 9.3. There was also an increase in mean GRS score from day 3 to months 6 and 12.Conclusion–A longitudinal microsurgical training course integrated within a hand surgery fellowship is associated with increased confidence and microsurgical skill. This study describes our approach and its feasibility.
Keywords: microsurgery; hand; curriculum; laboratory; educational; rat